Was ist ein Low Cost Airport? Ergebnisse einer vergleichenden Fluggastbefragung an den Flughäfen Frankfurt-Hahn und Bremen. - Klophaus, Richard; Schaper, Thorsten (Deutscher Verkehrs-Verl., 2004)
Die Frage nach den kennzeichnenden Eigenschaften einer Low Cost Airline wird schon seit geraumer Zeit in Wissenschaft und Praxis thematisiert. Parallel findet auch der Begriff "Low Cost Airport" zunehmend Verwendung (etwa in diversen Pressemitteilungen der Fraport AG zum "Flughafensystem Frankfurt (Main) - Frankfurt-Hahn"), ohne dass Low Cost Airports als Flughafenkategorie bislang eindeutig definiert wurden. Damit bleibt auch unklar, worin sich Low Cost Airports etwa von "Regionalflughäfen" oder "sekundären Flughäfen" abgrenzen. difu

It is becoming increasingly common practice to use the term 'low cost airport' although this definition is not official as yet. The difference between such an airport and a 'regional' or 'secondary' airport remains unclear. In this context, such criteria as lower airport charges and infrastructure costs, the airport's role in a point-to-point traffic pattern and its use by low cost airlines have to be taken into account. This report offers a new approach to the definition of a 'low cost airport' by way of reference to its clientele. For this purpose, a passenger survey has been carried out at Hahn airport, and its findings have been compared with a similar one at Bremen airport. The analysis has shown notable differences with regard to the socio-demographic structure and travel behaviour of passengers, and their acceptance of the services offered. difu
Keywords: Verkehr; Luftverkehr; Verkehrsinfrastruktur; Flughafen; Attraktivität; Einzugsbereich; Befragung; Fluggast; Billigflug; Fluggesellschaft; Luftverkehrsunternehmen; Passagieraufkommen; Verkehrsmarkt